Once upon a Deadpool [videorecording (DVD)] - Reese, Rhett; Wernick, Paul; Reynolds, Ryan; Reynolds, Ryan; Brolin, Josh; Baccarin, Morena; Savage, Fred, 1976-; Dennison, Julian, 2002-; Beetz, Zazie; Miller, T. J., 1981-; Hildebrand, Brianna, 1996-; Kesy, Jack (Twentieth Century Fox Home Entertainment, 2018)
A Deadpool fairy tale that gives zero F's.